THE INTERNALIZATION OF ISLAMIC CHARACTER EDUCATION IN ENGLISH LANGUAGE TEACHING - Amalul - Umam; Mohammad - Sahril (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
Strengthening character education (PPK) is one of the main features in the Curriculum 2013. This is something new for some teachers, especially pre-service teachers. This study investigated the understanding of pre-service teachers about Al-Zarnuji’s Islamic characters and the internalization of the characters during their learning processes. Observation, documentation and open-ended questionnaire were employed in the study. The findings showed that pre-service teachers were familiar with the characters and could internalize them. The study suggests that the internalization of characters needs to be integrated in the learning processes from which pre-service teachers get used to the characters.